Decoding attention control and selection in visual spatial attention. Issue 14 (16th June 2020) - Hong, Xiangfei; Bo, Ke; Meyyappan, Sreenivasan; Tong, Shanbao; Ding, Mingzhou
Abstract: Event‐related potentials (ERPs) are used extensively to investigate the neural mechanisms of attention control and selection. The univariate ERP approach, however, has left important questions inadequately answered. We addressed two questions by applying multivariate pattern classification to multichannel ERPs in two cued visual spatial attention experiments ( N = 56): (a) impact of cueing strategies (instructional vs. probabilistic) on attention control and selection and (b) neural and behavioral effects of individual differences. Following cue onset, the decoding accuracy (cue left vs. cue right) began to rise above chance level earlier and remained higher in instructional cueing ( 80 ms) than in probabilistic cueing ( 160 ms), suggesting that unilateral attention focus leads to earlier and more distinct formation of the attention control set. A similar temporal sequence was also found for target‐related processing (cued target vs. uncued target), suggesting earlier and stronger attention selection under instructional cueing. Across the two experiments: (a) individuals with higher cue‐related decoding accuracy showed higher magnitude of attentional modulation of target‐evoked N1 amplitude, suggesting that better formation of anticipatory attentional state leads to stronger modulation of target processing, and (b) individuals with higher target‐related decoding accuracy showed faster reaction times (or larger cueing effects), suggesting that stronger selection of task‐relevant information leads to better behavioral performance. Taken together, multichannel ERPs combined with machine learning decoding yields new insights into attention control and selection that complement the univariate ERP approach, and along with the univariate ERP approach, provides a more comprehensive methodology to the study of visual spatial attention. Abstract : Covert spatial attention can be decoded from multichannel event‐related potential patterns during both attention control (cue left vs. cue right) and attention selection (cued target vs. uncued target). Decoding accuracy (cue left vs. cue right) during attention control predicted the magnitude of attentional modulation of target‐related N1 component. Decoding accuracy (cued target vs. uncued target) during attention selection predicted behavioral performance.